The lichen-forming and lichenicolous fungi of the geological nature monument “Kam’yana Mogyla” (Zaporiz’ka oblast, Melitopol’skiy district) (CHORNOMORSKI BOTANICAL JOURNAL, 2008)
The list of the lichenbiota of the sandstone outcrops of geological nature monument “Kam’yana Mogyla” includes 46 species lichen-forming and 9 lichenocolous fungi of 33 genera, 23 families, 3 orders and mithosporic fungi. Among them Endococcus fusiger Th. Fr. & Almq., Intralichen lichenicola (M.S. Christ. & D. Hawksw.) D. Hawksw. & M.S. Cole та Vouauxiomyces ramalinae (Nordin) D. Hawksw. were firstly reported for Ukraine, Acarospora aff. hospitans H. Magn., Haematomma ochroleucum (Neck.) J. R. Laundon, Lecanora caesiosora Poelt, Miriquidica complanata (Körber) Hertel & Rambold, Lepraria neglecta (Nyl.) Erichsen, Protoparmelia montagnei (Fr.) Poelt & Nimis – new for plain part of Ukraine, and Lichenothelia scopularia (Nyl.) D. Hawksw. – for steppe part of Ukraine. The results of arealogical, phythoclimatical and lichenocoenothic analysis are provided.
Keywords: lichen-forming fungi, lichenicolous fungi, sandstone outcrops, geological nature monument “Kam’yana Mogyla”.